Deep Brain Stimulation of the Pedunculopontine Nucleus Area in Parkinson Disease: MRI-Based Anatomoclinical Correlations and Optimal Target. Issue 2 (25th May 2018) - Goetz, Laurent; Bhattacharjee, Manik; Ferraye, Murielle U; Fraix, Valérie; Maineri, Carina; Nosko, Daniela; Fenoy, Albert J; Piallat, Brigitte; Torres, Napoléon; Krainik, Alexandre; Seigneuret, Eric; David, Olivier; et al.
Abstract: BACKGROUND: Experimental studies led to testing of deep brain stimulation (DBS) of the pedunculopontine nucleus (PPN) as a new therapy to treat freezing of gait (FOG) in Parkinson disease (PD). Despite promising initial results fueling a growing interest toward that approach, several clinical studies reported heterogeneity in patient responses. Variation in the position of electrode contacts within the rostral brainstem likely contributes to such heterogeneity. OBJECTIVE: To provide anatomoclinical correlations of the effect of DBS of the caudal mesencephalic reticular formation (cMRF) including the PPN to treat FOG by comparing the normalized positions of the active contacts among a series of 11 patients at 1- and 2-yr follow-up and to provide an optimal target through an open-label study. METHODS: We defined a brainstem normalized coordinate system in relation to the pontomesencephalic junction. Clinical evaluations were based on a composite score using objective motor measurements and questionnaires allowing classification of patients as "bad responders" (2 patients), "mild responders" (1 patient) and "good responders" (6 patients). Two patients, whose long-term evaluation could not be completed, were excluded from the analysis. RESULTS: Most effective DBS electrode contacts to treat FOG in PD patients were located in the posterior part of the cMRF (encompassing the posterior PPN and cuneiform nucleus) at the level of the pontomesencephalic junction. CONCLUSION: In the present exploratory study, we performed an anatomoclinical analysis using a new coordinate system adapted to the brainstem in 9 patients who underwent PPN area DBS. We propose an optimal DBS target that allows a safe and efficient electrode implantation in the cMRF.